The Impact of eSports Industry Knowledge Alliances on Innovation Performance: A Mediation Model Based on Knowledge Sharing - Yue, Longfei; Zheng, Yiwen; Ye, Meng (Frontiers in Psychology, 2022)
This study investigates the associations among member ability, member relationships, knowledge sharing, and innovation performance in eSports industry knowledge alliance. A survey strategy and purposive sampling were applied, and the analysis was conducted on a sample of 311 senior managers from the China eSports Association. The hypotheses were tested using SPSS 24.0 software and AMOS 24.0 software. This study shows that member ability and member relationships have both a direct and indirect effect on innovation performance. Firstly, member ability, member relationships, and member knowledge sharing significantly impact the innovation performance of eSports industry knowledge alliances. Secondly, member knowledge sharing plays a mediating role in the effect of member ability and membership relationship on innovation performance. This pioneering article explores the interaction mechanisms between member ability, member relationships, and innovation performance in eSports industry knowledge alliance. The research results are conducive to the development of the eSports industry towards deep integration and sustainable development and provide a reference for similar knowledge-intensive enterprise alliance behaviours.